Germination of seeds and production of seedlings of lettuce cultivars at different substrates - Da Silva, Elisângela Aparecida; Mendonça, Vander; Da Silva Tosta, Mauro; De Oliveira, Alessandra Conceição [UNESP]; Dos Reis, Luis Lessi; Bardiviesso, Diógenes Martins (Universidade Estadual de Londrina, 2008)
The aim of this paper was to evaluate the effects of the combinations of substrata on germination and development of seedlings of lettuce cultivars. The experiment was carried out in a nursery, in Mato Grosso do Sul State University. There were compared the following combinations of substrata: washed sand + earthworm humus (2:1); manure bovine + earthworm humus (2:1); Plantmax® + earthworm humus (2:1); washed sand + Plantmax® (2:1) and manure bovine + Plantmax® (2:1), and three lettuce cultivars: Crespa sem cabeça, Americana Júlia and Babá de Verão. The experimental design was entirely at random, in a 5×3 factorial outline, with four replications and 16 seeds per plot. There were considered for evaluation10 central seedlings per plot. The characteristics evaluated were: germination percentage (%), index of germination speed (IVE) and dry mass of the whole seedling (g). For all the analyzed variables, the cultivars Babá de Verão and Crespa sem cabeça presented the best results. Manure + humus was the best substratum to obtain seedling with larger development (vigor), althout it did not increase IVE and germination percentage.
Germinação da semente e produção de mudas de cultivares de alface em diferentes substratos
Keywords: Earthworm humus; Lactuca sativa L.; Seedlings production